E-Marketplace Development With C2C Model And Appreciative Inquiry - Bambang Agus Herlambang; Muhammad Saifuddin Zuhri; Dwi Nuvitalia (Jurnal Transformatika, 2018)
People's lifestyles change in spending their funds have changed. Trend of software development innovation in Indonesia could be mapped into several types of E-Commerce, Media, Transportation, Accommodation and Logistics and Education. Now, there are 45 young entrepreneurs at the University PGRI Semarang. They need a tool to maximize business transactions, so it is necessary to develop E-Marketplace. The E-Marketplace Application System will be integrated with the Apprecitive Inquiry concept to reward users who frequently perform activities on the E-Marketplace application system. UML (Unifield Modeling Language) was used as a tool in designing this system. The result of this research is E-Marketplace application system that can run on web and mobile (hybrid) platform so it is expected to be a new marketing tool for young entrepreneurs at UPGRIS.